A preliminary investigation of the essential oil of Citrus grandis Osbeck (Fam. Rutaceae) - Go, Zenaida O.; Bernal-Santos, Rizalina (Quezon City Department of Pharmacy, College of Pharmacy, University of the Philippines Diliman, 1977)
The volatile oil obtained by distillation from the peels of Citrus grandis Osbeck was a very pale yellow liquid having an odor somewhat similar to lemon oil. The average yield was 1.3% volume by weight. The oil had the following physicochemical properties: specific gravity at 26°, 0.8464; optical rotation at 29°, +92.0026; refractive index at 26°, 1.47058; 1 part was soluble in 1 part of non-polar solvents; acid value, 2.32. Analysis by TLC developed by a mixture of 9.5:0.5 benzene:acetone gave 10 spots. It was possible to isolate some of the constituents using column chromatography and preparative TLC. The isolated components analyzed by spectrophotometry and TLC were identified as possible d-limonene, ∝-pinene, and a terpene acetat
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Diliman, 1977.
Keywords: Essences and essential oil; Citru